IPO Pricing and the Relative Importance of Investor Sentiment: Evidence from Germany - Andreas Oehler; Marco Rummer; Peter N. Smith (Otto-Friedrich-Universität Bamberg, Lehrstuhl für Betriebswirtschaftslehre, insbesondere Finanzwirtschaft, 2004)
The underpricing phenomenon of Initial Public Offerings (IPOs) has been widely studied across different stock markets around the world and has often been explained to be as a result of asymmetrically distributed information and ex-ante uncertainty. However, as Ritter and Welch (2002) argue to the contrary, these theories are unlikely to explain the persistent pattern of high initial returns during the first trading day as well as other features of the returns data. This paper add some further alternative explanations to the traditional theory while focusing on German IPOs during the 1997 to 2001 period and covering a sample of 410 firms. Using time series regressions the cyclical behaviour of the issue activity is examined and we report, using VAR analysis, that lagged underpricing and IPO volume influence the decision to go public. The cross-sectional regression analysis, using both censored and uncensored data, shows that the initial returns are mainly influenced by investor sentiment and demand, and less by ex-ante uncertainty, especially during the dot-com boom.
Keywords: G12; G32; G24; G10; 330; Initial Public Offerings (IPO); Underpricing; Investor Sentiment; Hot-issue Markets; Ex-ante Uncertainty